THE RELATIONSHIP BETWEEN MULTIPLE INTELLIGENCES AND READING COMPREHENSION ACHIEVEMENT OF THE ELEVENTH GRADE STUDENTS’ OF SMA NEGERI 8 PALEMBANG - Hervin A.R.N. A.R.N. (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2016)
Abstract: The objectives of this study were to find out : (1) How multiple intelligences of the students look like, (2) How reading achievement of the students looks like, (3) Whether or not there is a significant correlation between multiple intelligences and reading comprehension achievement of the students (4) How much multiple intelligences contribute to reading comprehension achievement of the students and (5) Which type of multiple intelligences singnificantly influence reading achievement of the students most. The study was correlational with univariate and bivariate analyses. The sample was the eleventh grade students of SMA Negeri 8 Palembang with the total number 157 students. To collect the data and to measure students’ multiple intellgences and reading comprehension achievement, a questionnaire and reading test were given. The result showed that intelligence that students had the most was interpersonal and reading comprehension achievement of the students was low. There was no significant correlation between multiple intelligences and reading comprehension achievement with the r-obtained was lower than value of r-table (0.150 < 0.159) at the 0.05 level (2-tailed) and p value (0.066) was higher than (0.05). Then, it was found that the multiple intelligences only contributed 19.2% to reading comprehension achievement and the intelligence which significantly contributed to reading comprehension achievement was logical-mathematics as the higest. Keywords: Correlation, Multiple Intelligences, Reading Comprehension Achievement